(untitled) (Journal of Plant Disease Sciences, 2025)
The present investigation aimed to evaluate the cultivation of Pleurotus sajor-caju on various agro-waste substrates, including soybean straw, wheat straw, paddy straw, sawdust, sugarcane bagasse, banana leaves, bajra straw, and green gram straw. The nutritional composition of these substrates was analyzed before and after mushroom cultivation.Additionally, the study explored the reuse of spent mushroom substrate (SMS) by incorporating it into fresh substrate mixtures at different proportions. Among the tested combinations, 100% soybean straw and 20:80 (SMS + soybean straw) resulted in the highest yield of fresh mushrooms, superior biological efficiency, larger stipe and pileus size, increased pinhead formation, and enhanced fruiting body development. These combinations also required the shortest duration for vegetative and reproductive growth.The findings indicate that spent mushroom substrate can be effectively recycled in combination with soybean straw to support sustainable mushroom cultivation. Spent Mushroom Substrate (SMS) is a valuable by-product with potential applications in organic farming, composting, soil enrichment, biofuel production, and agricultural sustainability. It offers a promising alternative for reducing agricultural waste while enhancing soil fertility and crop productivity.